The Role of Corporate Culture in the Financial Industry - Andreas Barth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the role of corporate culture in the financial industry. Theoretical literature emphasizes the role of corporate culture in the sorting process of workers into firms. We take this argument to the empirics and analyze whether banks that differ in their corporate culture use different compensation schemes in order to attract a specific type of workers. In a second step, we combine the role of corporate culture with the literature on CEO compensation and risk-taking and analyze empirically the impact of corporate culture on banks' risk-taking as well as on banks' performance. More precisely, we argue that the incentives arising from CEO compensation schemes are diluted once we control for the self-sorting mechanism of CEOs in firms with different corporate cultures. We find that CEOs of banks with a strong competition-oriented corporate culture have a larger share of variable payments in their total compensation. Moreover, we find that a more competition-oriented corporate culture is associated with a higher credit risk as well as with a higher buy-and-hold stock market return.
Keywords: G21; G34; M14; 330